A comparison of flood cooling, minimum quantity lubrication and high pressure coolant on machining and surface integrity of titanium Ti-5553 alloy - KAYNAK, YUSUF (ELSEVIER SCI LTD, 2018)
Ti-5553 alloy is considered as a next generation aerospace alloy, however, it is also considered as difficult-to machine material due to its thermal and mechanical properties. As limited research work presented in literature on machining process of this alloy, more research is needed to determine appropriate machining strategies for this alloy. Thus, this study presents extensive experimental work to asses the machining performance of this next generation aerospace alloy in a wide range of cutting speeds by utilizing high pressure coolant (HPC) delivery, minimum quantity lubrication (MQL), and flood cooling. Machining performance measures are tool wear rate, force components, and chip breaking. Surface and subsurface characteristics of machined parts were evaluated focusing on surface topography, dimensional accuracy, microhardness and XRD analysis. The obtained results showed that high pressure coolant delivery remarkable improved machining performance of this alloy at higher cutting speeds as compared to flood cooling and MQL. Considering surface integrity characteristics, surface and subsurface hardness shows decreased trend in all conditions and cutting speeds as compared to hardness of as received material resulting from thermal softening. XRD analysis illustrated that alfa and beta peaks shows noticeable broadening and reduced intensity but no phase transformation is observed.
Keywords: High pressure coolant delivery; Machining performance; Surface integrity; Titanium Ti-5553 alloy; TOOL-WEAR; CHIP FORMATION; MACHINABILITY; PERFORMANCE; MQL; MICROSTRUCTURE; TI-6AL-4V; BEHAVIOR; CARBIDE; DRY